Confronting Christianity: 12 hard questions for the world's largest religion. - Maclaughlin Rebecca (Illinois Crossway, 2019)
The book helps in confronting Christianity and one's worldviews, hopes, fears, failures and serach for identity and satisfaction.
Keywords: Apologetics, Bible-Theology